Carbon fiber composite material as well as preparation method and application thereof

By assembling liquid crystal polymers of different dimensions on the surface of carbon fiber and establishing a multi-dimensional thermal conductivity network, the problem of poor interface bonding strength and thermal conductivity of carbon fiber composite materials is solved, and the coordinated improvement of interface and thermal conductivity is achieved.

CN119220055AActive Publication Date: 2024-12-31BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411494879.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-31
Estimated Expiration
2044-10-24

Smart Images

  • Figure CN119220055A_ABST
    Figure CN119220055A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon fiber composite material as well as a preparation method and application thereof. Based on the structural design of the liquid crystal polymer with different dimensions, a liquid crystal polymer molecule assembly layer is constructed on the surface of the carbon fiber, the roughness and surface activity of the surface of the carbon fiber are improved, and meanwhile, the interface performance of the composite material is improved through the efficient redirectionality of the liquid crystal polymer under the microcosmic mesocrystal domain structure and the load. Besides, based on the high orientation of the liquid crystal polymer in the interface phase of the composite material, a multi-dimensional heat conduction network is constructed, the dominant vibration mode of the carbon fiber and the resin matrix in the phonon heat transfer process is effectively coupled, the possibility of carrier phonon scattering at the interface is reduced, the interface thermal resistance is greatly reduced, and the thermal conductivity of the composite material is improved. Therefore, the heat-conducting property of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite material preparation, and in particular relates to a carbon fiber composite material and a preparation method and application thereof. Background Art

[0002] The structural and functional integration of carbon fiber composites is a development trend in the fields of aerospace, precision instruments, vehicle structural parts or electronic devices. However, carbon fiber usually has a high degree of graphitization, and its surface is chemically inert, resulting in poor interfacial wettability and compatibility between the fiber and the resin matrix, which affects the interfacial bonding of the composite material. In addition, due to the difference in the molecular arrangement of carbon fiber and resin matrix, the coupling degree of the vibration mode that dominates phonon heat transfer is low, which leads to the generation of interfacial thermal resistance and reduces the thermal conductivity of the composite material. In order to simultaneously improve the interface and thermal conductivity of the composite material, carbon nanoparticles are usually introduced on the surface of carbon fiber to construct a thermal conduction path. The literature (Composites Part A, 2018, 106: 1-10) introduces graphene nanosheets into the interface phase of the composite material, which effectively improves the interface bonding strength while taking into account the improvement of the out-of-plane thermal conductivity of the composite material. However, the vibration mode of phonon heat transfer of carbon nanoparticles is still significantly different from that of the resin matrix, which leads to the generation of interfacial thermal resistance between carbon nanoparticles and the resin matrix; at the same time, carbon nanoparticles are easy to agglomerate at the interface of the composite material, causing more serious interface defects.

[0003] Chinese patent application number CN202211270384.X constructs a composite material interface assembly transition layer based on the π-π stacking effect between aromatic condensed ring molecules and graphene and the carbon fiber surface, thereby improving the interface bonding strength of the composite material. At the same time, the introduction of aromatic condensed ring molecules alleviates the agglomeration effect of graphene at the interface, improves the phonon transmission efficiency of the interface heat conduction path, and improves the thermal conductivity of the composite material. However, the assembly between the carbon nanoparticles and aromatic condensed ring molecules alternately introduced in the interface phase due to the π-π conjugation effect will still agglomerate on the carbon fiber surface, thereby affecting the interface bonding; at the same time, the amorphous structure of the aromatic condensed ring molecules is not conducive to suppressing the occurrence of carrier phonon scattering, thereby limiting the improvement of the thermal conductivity of the composite material.

[0004] Therefore, it is still necessary to develop suitable organic polymers to construct a high-performance thermal conductive interface phase on the carbon fiber surface to overcome the above problems. Summary of the invention

[0005] In order to solve at least some of the technical problems in the above-mentioned prior art, the present invention assembles liquid crystal polymers of different dimensions on the surface of carbon fiber, and enhances the interface performance of the composite material with its microscopic mesomorphous domain structure and efficient reorientation under load. At the same time, based on the high orientation of the liquid crystal polymer after the composite material is cured, a multi-dimensional thermal conductive network of phonon heat transfer is established to achieve a synergistic improvement of the interface and thermal conductivity of the composite material. Specifically, the present invention includes the following contents.

[0006] A first aspect of the present invention provides a method for preparing a carbon fiber composite material, comprising the following steps:

[0007] (1) dissolving an aromatic dianhydride and an organic aromatic amine in a first solvent, reacting at 70-120° C. for 8-14 hours to obtain a first liquid crystal polymer, and / or dissolving an aromatic polyphenol and an organic halogenated hydrocarbon in a second solvent, adjusting the pH value to alkaline, and reacting at 50-80° C. for 24-48 hours to obtain a second liquid crystal polymer, and dissolving the first liquid crystal polymer and / or the second liquid crystal polymer in a third solvent to obtain a liquid crystal polymer assembly solution;

[0008] (2) assembling the liquid crystal polymer assembly liquid and the unsized carbon fiber at 60-120° C. for 1-3 hours to obtain carbon fiber with surface modified by liquid crystal polymer;

[0009] (3) heating and curing the modified carbon fiber and the epoxy resin / curing agent system to obtain the carbon fiber composite material.

[0010] In certain embodiments, according to the method for preparing a carbon fiber composite material described in the present invention, the aromatic dianhydride includes at least one of isomellitic dianhydride, naphthalenetetracarboxylic dianhydride and perylenetetracarboxylic dianhydride; the organic aromatic amine includes at least one of octyl p-aminobenzoate, isooctyl p-aminobenzoate and hexyl p-aminobenzoate; the aromatic polyphenol includes at least one of hydroxybenzanthracene, hydroxybenzoacenaphthene, hydroxytriphenylene and hydroxybenzocoronene; the organic halogenated hydrocarbon includes at least one of 1-bromooctane, isooctane bromide and 1-bromohexane; the first solvent includes at least one of methanol, ethanol and acetonitrile; the second solvent includes at least one of N,N-dimethylformamide, propanol and tetrahydrofuran; the third solvent includes at least one of propylene glycol, n-butanol and dichloromethane.

[0011] In certain embodiments, according to the method for preparing a carbon fiber composite material of the present invention, the molar ratio of the aromatic dianhydride to the organic aromatic amine is 1:(2-6), the molar ratio of the aromatic polyphenol to the organic halogenated hydrocarbon is 1:(4-10), and the mass fraction of the liquid crystal polymer in the liquid crystal polymer assembly solution is 0.5-5wt%.

[0012] In certain embodiments, according to the method for preparing a carbon fiber composite material of the present invention, the first liquid crystal polymer includes at least one of phthalimide, naphthylimide and perylene imide, and the second liquid crystal polymer includes at least one of alkoxybenzanthracene, alkoxybenzoacenaphthene, alkoxytriphenylene and alkoxybenzocoronene.

[0013] In certain embodiments, according to the method for preparing a carbon fiber composite material of the present invention, the first liquid crystal polymer is a one-dimensional rod-like liquid crystal polymer, and the second liquid crystal polymer is a two-dimensional disc-like liquid crystal polymer.

[0014] In certain embodiments, according to the method for preparing a carbon fiber composite material of the present invention, the pH value is adjusted by an alkaline solution, and the alkaline solution includes at least one of a potassium hydroxide solution, a sodium hydroxide solution, a potassium carbonate solution, and a triethylamine solution.

[0015] In certain embodiments, the method for preparing a carbon fiber composite material according to the present invention further comprises a step of purifying the second liquid crystal polymer.

[0016] In certain embodiments, according to the method for preparing a carbon fiber composite material of the present invention, the reagent used for purification includes at least one of a sodium carbonate solution, a sodium bicarbonate solution and ethyl acetate.

[0017] In certain embodiments, according to the method for preparing a carbon fiber composite material of the present invention, wherein in the modified carbon fiber, the mass ratio of the liquid crystal polymer to the unsized carbon fiber is 1:(20-200).

[0018] In certain embodiments, according to the method for preparing a carbon fiber composite material of the present invention, the unsized carbon fiber includes at least one of high-strength carbon fiber, high-strength medium-modulus carbon fiber and high-strength high-modulus carbon fiber; the epoxy resin includes at least one of hydrogenated bisphenol A epoxy resin, aliphatic glycidyl ether epoxy resin, epoxidized olefin epoxy resin and alicyclic epoxy resin; the curing agent includes at least one of aliphatic polyamine and alicyclic polyamine.

[0019] A second aspect of the present invention provides a carbon fiber composite material, which is prepared according to the preparation method described in the first aspect of the present invention.

[0020] A third aspect of the present invention provides use of the carbon fiber composite material according to the present invention in aerospace materials, precision instruments, vehicle structural parts or electronic device materials.

[0021] Based on the structural design of liquid crystal polymers of different dimensions, the present invention constructs a liquid crystal polymer molecular assembly layer on the surface of carbon fiber, improving the roughness and surface activity of the carbon fiber surface; at the same time, the liquid crystal polymer achieves the improvement of the interface performance of the composite material with its microscopic mesomorphous domain structure and efficient reorientation under load. In addition, based on the highly oriented structure of the liquid crystal polymer molecular assembly layer of different dimensions, the present invention constructs a multi-dimensional thermal conductive network of the composite material interface phase, effectively coupling the dominant vibration mode of the carbon fiber and the resin matrix in the phonon heat transfer process, reducing the possibility of carrier phonon scattering at the interface, greatly reducing the interface thermal resistance, and thus improving the thermal conductivity of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The surface morphology of the carbon fiber modified by the liquid crystal polymer of the present invention is shown, wherein A and B are scanning electron microscope (SEM) images of the surface of the one-dimensional rod-shaped and two-dimensional disk-shaped liquid crystal polymer modified carbon fiber, respectively.

[0023] Figure 2 The interfacial shear strength of the monofilament composite material of the present invention is shown.

[0024] Figure 3 The thermal conductivity in the thickness direction of the unidirectional composite material of the present invention is shown. DETAILED DESCRIPTION

[0025] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0026] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that the upper and lower limits of the scope and each intermediate value therebetween are specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0027] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art to which the invention belongs. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0028] Preparation method

[0029] One aspect of the present invention provides a method for preparing a carbon fiber composite material. The preparation method of the present invention can improve the interface properties and thermal conductivity of the carbon fiber composite material. Therefore, the method of the present invention can also be called "a method for simultaneously improving the interface properties and thermal conductivity of the carbon fiber composite material."

[0030] In a preferred embodiment, the method of the present invention comprises the following steps:

[0031] (1) dissolving an aromatic dianhydride and an organic aromatic amine in a first solvent, reacting at 70-120° C., preferably 75-115° C., and more preferably 80-110° C., such as 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., and 110° C. for 8-14 h, preferably 9-12 h, such as 9, 10, 11, and 12 h, to obtain a first liquid crystal polymer, and / or dissolving an aromatic polyphenol and an organic halogenated hydrocarbon in a second solvent, adjusting the pH value to alkaline, preferably adjusting the pH value to 8-11, such as 8, 9, 10, and 11, and reacting at 5 0-80°C, preferably 55-75°C, and preferably 60-70°C, for example 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, react for 24-48h, preferably 24-40h, and preferably 24-35h, for example 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35h, to obtain a second liquid crystal polymer, and dissolve the first liquid crystal polymer and / or the second liquid crystal polymer in a third solvent to obtain a liquid crystal polymer assembly solution;

[0032] (2) assembling the liquid crystal polymer assembly liquid and the unsized carbon fiber at 60-120° C., preferably 60-110° C., and also preferably 60-100° C., for example, 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., and 100° C. for 1-3 h, for example, 1, 1.5, 2, 2.5, and 3 h, and vacuum drying to obtain carbon fiber modified with a surface liquid crystal polymer;

[0033] (3) heating and curing the modified carbon fiber and the epoxy resin / curing agent system to obtain the carbon fiber composite material. The "heat curing" is not particularly limited and can be performed using a heat-curable system and heating temperature known in the art. The specific components, parameters and heating equipment used can be adjusted according to actual needs.

[0034] In step (1) of the present invention, the aromatic dianhydride includes but is not limited to at least one of pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride and perylenetetracarboxylic dianhydride; the organic aromatic amine includes but is not limited to at least one of octyl p-aminobenzoate, isooctyl p-aminobenzoate and hexyl p-aminobenzoate; the aromatic polyphenol includes but is not limited to at least one of hydroxybenzanthracene, hydroxybenzoacenaphthene, hydroxytriphenylene and hydroxybenzocoronene; the organic halogenated hydrocarbon includes but is not limited to at least one of 1-bromooctane, isooctane bromide and 1-bromohexane; the first solvent includes but is not limited to at least one of methanol, ethanol and acetonitrile; the second solvent includes but is not limited to at least one of N,N-dimethylformamide, propanol and tetrahydrofuran; the third solvent includes but is not limited to at least one of propylene glycol, n-butanol and dichloromethane.

[0035] In order to obtain a carbon fiber composite material with synergistically improved interface performance and thermal conductivity, it is necessary to select a suitable liquid crystal polymer to modify the carbon fiber. In addition, the ratio of the reaction raw materials and the reaction conditions need to be controlled within an appropriate range. In a preferred embodiment, the molar ratio of aromatic dianhydride to organic aromatic amine is 1: (2-6), such as 1: 2, 1: 3, 1: 4, 1: 5, 1: 6, etc. In another preferred embodiment, the molar ratio of aromatic polyphenol to organic halogenated hydrocarbon is 1: (4-10), such as 1: 4, 1: 5, 1: 6, 1: 7, 1: 8, 1: 9, 1: 10, etc. The above-mentioned range is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] In order to obtain a carbon fiber composite material with synergistically improved interface performance and thermal conductivity, the concentration of the liquid crystal polymer assembly solution modified by the carbon fiber should not be too high or too low. In a preferred embodiment, the mass fraction of the liquid crystal polymer in the liquid crystal polymer assembly solution is 0.5-5wt%, preferably 0.5-4wt%, further preferably 0.5-3wt%, more preferably 0.5-2wt%, such as 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] In the present invention, the first liquid crystal polymer includes but is not limited to at least one of phthalimide, naphthalimide and perylene imide; the second liquid crystal polymer includes but is not limited to at least one of alkoxybenzanthracene, alkoxybenzoacenaphthene, alkoxytriphenylene and alkoxybenzocoronene. In a specific embodiment, the first liquid crystal polymer is naphthalimide. In another specific embodiment, the second liquid crystal polymer is alkoxytriphenylene.

[0038] In a preferred embodiment, the first liquid crystal polymer is a one-dimensional rod-shaped liquid crystal polymer. In another preferred embodiment, the second liquid crystal polymer is a two-dimensional disc-shaped liquid crystal polymer.

[0039] In a preferred embodiment, the pH value is adjusted to 8-11 by an alkaline solution, and the alkaline solution includes but is not limited to at least one of potassium hydroxide solution, sodium hydroxide solution, potassium carbonate solution and triethylamine solution. In a specific embodiment, the alkaline solution is sodium hydroxide solution.

[0040] In a preferred embodiment, the step of purifying the second liquid crystal polymer is further included, wherein the reagent used for purification includes but is not limited to at least one of sodium carbonate solution, sodium bicarbonate solution and ethyl acetate. In a specific embodiment, the reagent used for purification is sodium carbonate solution and ethyl acetate.

[0041] In order to obtain a carbon fiber composite material with synergistically improved interface performance and thermal conductivity, it is necessary to control the mass ratio of liquid crystal polymer to unsized carbon fiber in the modified carbon fiber within an appropriate range. In a preferred embodiment, the mass ratio of liquid crystal polymer to unsized carbon fiber is 1: (20-200), preferably 1: (40-150), and also preferably 1: (50-100), such as 1: 50, 1: 55, 1: 60, 1: 65, 1: 70, 1: 75, 1: 80, 1: 85, 1: 90, 1: 95, 1: 100, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In the present invention, the unsized carbon fiber includes but is not limited to at least one of high-strength carbon fiber, high-strength medium modulus carbon fiber and high-strength high modulus carbon fiber; the epoxy resin includes but is not limited to at least one of hydrogenated bisphenol A epoxy resin, aliphatic glycidyl ether epoxy resin, epoxidized olefin epoxy resin and alicyclic epoxy resin; the curing agent includes but is not limited to at least one of aliphatic polyamines (such as but not limited to ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, etc.) and alicyclic polyamines (such as but not limited to 1,3-bisaminomethylcyclohexane, p-aminodicyclohexylmethane, isophoronediamine, etc.).

[0043] Carbon fiber composites

[0044] In one aspect of the present invention, a carbon fiber composite material is provided, which is prepared according to the preparation method of the present invention. Preferably, the composite material of the present invention has an interface shear strength of not less than 100 MPa according to an interface shear performance test and a thermal conductivity of not less than 2 W / m·K in the thickness direction according to a laser flash test.

[0045] application

[0046] One aspect of the present invention provides the use of carbon fiber composite materials in aerospace structural functional integrated materials, precision instruments, vehicle body structural parts or electronic devices.

[0047] In the present invention, vehicle structural parts include structural parts of the vehicle body (including but not limited to the frame, roof, doors, etc.), chassis parts (including but not limited to the engine base, transmission housing), seats, interior decoration, etc.

[0048] In the present invention, aerospace materials include, but are not limited to, fuselage structures (such as wings, fuselages), engine components (such as turbine blades, engine casings, etc.), and spacecraft structures (such as satellite brackets, space telescope brackets, etc.).

[0049] In the present invention, precision instruments include any devices or structural parts containing carbon fiber that can achieve precise measurement and detection, such as mechanical properties testing devices used in the fields of material science research, product quality control, etc., such as tensile strength and bending strength testing machines, and also include other qualitative or quantitative instruments used for scientific research, such as metallographic microscopes, X-ray diffractometers, time-of-flight mass spectrometers, scanning electron microscopes, thermogravimetric analyzers, etc.

[0050] Example 1

[0051] This example shows the preparation method of carbon fiber composite material and the performance test results.

[0052] 1. Preparation method

[0053] (1) Synthesis of one-dimensional liquid crystal polymer and preparation of assembly solution: 1,4,5,8-naphthalenetetracarboxylic dianhydride and isooctyl p-aminobenzoate were dissolved in N,N-dimethylformamide at a molar ratio of 1:2 and reacted at 110°C for 12 h to obtain a one-dimensional rod-shaped naphthylimide liquid crystal polymer, which was then dissolved in propylene glycol to obtain a liquid crystal polymer assembly solution, in which the mass fraction of the liquid crystal polymer was 1.0 wt%.

[0054] (2) Preparation of carbon fiber modified by liquid crystal polymer assembly: Unsized high-strength medium-modulus carbon fiber (T800H, domestically produced) and the above-mentioned liquid crystal polymer assembly liquid are placed in a hydrothermal autoclave and assembled at 100°C for 2 hours. After vacuum drying, carbon fiber modified by surface liquid crystal polymer assembly is obtained, wherein the mass fraction of the liquid crystal assembly layer is 1.5wt% of the above-mentioned unsized carbon fiber.

[0055] (3) Preparation of carbon fiber composite materials: Compounding the modified carbon fiber with an alicyclic epoxy resin / alicyclic polyamine curing agent system, heating according to a curing system, and obtaining a carbon fiber composite material with synergistically improved interface and thermal conductivity properties.

[0056] 2. Performance test results

[0057] According to the interface shear performance test, the interface shear strength of the single-filament composite material is 101.58MPa. According to the laser flash test, the thermal conductivity of the unidirectional composite material in the thickness direction is 2.70W / m·K.

[0058] Example 2

[0059] This example shows the preparation method of carbon fiber composite material and the performance test results.

[0060] 1. Preparation method

[0061] (1) Synthesis of two-dimensional liquid crystal polymer and preparation of assembly solution: 2,3,6,7,10,11-hexahydroxybenzophenone and isooctane bromide were dissolved in ethanol at a molar ratio of 1:8, the pH value was adjusted to 10 with NaOH solution, and the reaction was carried out at 70°C for 24 h. A two-dimensional disc-like alkoxybenzophenone liquid crystal polymer was obtained by extraction with NaHCO3 and ethyl acetate, and the two-dimensional disc-like alkoxybenzophenone liquid crystal polymer was dissolved in dichloromethane to obtain a liquid crystal polymer assembly solution.

[0062] (2) Preparation of carbon fiber modified by liquid crystal polymer assembly: Unsized high-strength high-modulus carbon fiber (M40X, domestic) and the above-mentioned liquid crystal polymer assembly liquid were placed in a hydrothermal autoclave, assembled at 60°C for 3 hours, and vacuum dried to obtain carbon fiber modified by surface liquid crystal polymer assembly. The mass fraction of the liquid crystal assembly layer is 2wt% of the above-mentioned unsized carbon fiber.

[0063] (3) Preparation of carbon fiber composite materials: Compounding the modified carbon fiber with a hydrogenated bisphenol A epoxy resin / aliphatic polyamine curing agent system, heating according to a curing system, and obtaining a carbon fiber composite material with synergistically improved interface and thermal conductivity properties.

[0064] 2. Performance test results

[0065] According to the interface shear performance test, the interface shear strength of the single-filament composite material is 116.90MPa. According to the laser flash test, the thermal conductivity of the unidirectional composite material in the thickness direction is 3.14W / m·K.

[0066] Comparative Example 1

[0067] This comparative example shows the preparation method of the carbon fiber composite material and the performance test results.

[0068] 1. Preparation method

[0069] Unsized high-strength medium modulus carbon fiber (T800H, domestically produced) was compounded with hydrogenated bisphenol A epoxy resin / aliphatic polyamine curing agent system and heated according to the curing system to obtain a carbon fiber composite material.

[0070] 2. Performance test results

[0071] According to the interface shear performance test, the interface shear strength of the single-filament composite material is 64.11MPa. According to the laser flash test, the thermal conductivity of the unidirectional composite material in the thickness direction is 1.38W / m·K.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a carbon fiber composite material, characterized in that: The following steps are involved: (1) dissolving an aromatic dianhydride and an organic aromatic amine in a first solvent, reacting at 70-120° C. for 8-14 hours to obtain a first liquid crystal polymer, and / or dissolving an aromatic polyphenol and an organic halogenated hydrocarbon in a second solvent, adjusting the pH value to alkaline, and reacting at 50-80° C. for 24-48 hours to obtain a second liquid crystal polymer, and dissolving the first liquid crystal polymer and / or the second liquid crystal polymer in a third solvent to obtain a liquid crystal polymer assembly solution; (2) assembling the liquid crystal polymer assembly liquid and the unsized carbon fiber at 60-120° C. for 1-3 hours to obtain carbon fiber with surface modified by liquid crystal polymer; (3) heating and curing the modified carbon fiber and the epoxy resin / curing agent system to obtain the carbon fiber composite material.

2. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The aromatic dianhydride includes at least one of pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride and perylenetetracarboxylic dianhydride; the organic aromatic amine includes at least one of octyl p-aminobenzoate, isooctyl p-aminobenzoate and hexyl p-aminobenzoate; the aromatic polyphenol includes at least one of hydroxybenzanthracene, hydroxybenzoacenaphthene, hydroxytriphenylene and hydroxybenzocoronene; the organic halogenated hydrocarbon includes at least one of 1-bromooctane, isooctane bromide and 1-bromohexane; the first solvent includes at least one of methanol, ethanol and acetonitrile; the second solvent includes at least one of N,N-dimethylformamide, propanol and tetrahydrofuran; the third solvent includes at least one of propylene glycol, n-butanol and dichloromethane.

3. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The molar ratio of the aromatic dianhydride to the organic aromatic amine is 1:(2-6), the molar ratio of the aromatic polyphenol to the organic halogenated hydrocarbon is 1:(4-10), and the mass fraction of the liquid crystal polymer in the liquid crystal polymer assembly solution is 0.5-5wt%.

4. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The first liquid crystal polymer includes at least one of phthalimide, naphthalimide and perylene imide, and the second liquid crystal polymer includes at least one of alkoxybenzanthracene, alkoxybenzoacenaphthene, alkoxytriphenylene and alkoxybenzocoronene; Preferably, the first liquid crystal polymer is a one-dimensional rod-shaped liquid crystal polymer, and the second liquid crystal polymer is a two-dimensional disc-shaped liquid crystal polymer.

5. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The pH value is adjusted by an alkaline solution, wherein the alkaline solution includes at least one of a potassium hydroxide solution, a sodium hydroxide solution, a potassium carbonate solution and a triethylamine solution.

6. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The method further comprises the step of purifying the second liquid crystal polymer; Preferably, the reagent used for purification includes at least one of sodium carbonate solution, sodium bicarbonate solution and ethyl acetate.

7. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: In the modified carbon fiber, the mass ratio of the liquid crystal polymer to the unsized carbon fiber is 1:(20-200).

8. The method for preparing a carbon fiber composite material according to claim 1, characterized in that: The unsized carbon fiber includes at least one of high-strength carbon fiber, high-strength medium-modulus carbon fiber and high-strength high-modulus carbon fiber; the epoxy resin includes at least one of hydrogenated bisphenol A epoxy resin, aliphatic glycidyl ether epoxy resin, epoxidized olefin epoxy resin and alicyclic epoxy resin; the curing agent includes at least one of aliphatic polyamine and alicyclic polyamine.

9. A carbon fiber composite material, characterized in that: The preparation method is obtained according to any one of claims 1 to 8.

10. Use of the carbon fiber composite material according to claim 9 in aerospace materials, precision instruments, vehicle structural parts or electronic devices.

Citation Information

Patent Citations

  • Method for modifying carbon fiber surface by assembly of aromatic fused ring molecules and preparation method of carbon fiber interface reinforced resin matrix composite

    CN109338730A

  • Preparation method of carbon fiber composite material

    CN109851999A

  • Heat-conducting filler, preparation method, resin composite material containing heat-conducting filler and application of resin composite material

    CN114149616A

  • Pitch-based carbon fiber composite material with heat-conducting interface as well as preparation method and application thereof

    CN115838526A

Cited By

  • Carbon fiber directionally-distributed high-thermal-conductivity sealing paste and preparation method thereof

    CN120518981A

  • High-strength fiber composite material and preparation method thereof

    CN121136347A

  • Carbon fiber composite material with synergistically improved interface and heat-conducting property as well as preparation method and application of carbon fiber composite material

    CN121949978A